2018
DOI: 10.1186/s12934-018-1004-x
|View full text |Cite
|
Sign up to set email alerts
|

Co-culture of Bacillus amyloliquefaciens ACCC11060 and Trichoderma asperellum GDFS1009 enhanced pathogen-inhibition and amino acid yield

Abstract: BackgroundBacillus spp. are a genus of biocontrol bacteria widely used for antibiosis, while Trichoderma spp. are biocontrol fungi that are abundantly explored. In this study, a liquid co-cultivation of these two organisms was tried firstly.Results and discussionThrough liquid chromatography-mass spectrometry/mass spectrometry (LC–MS/MS), it was discovered that with an inoculation in the ratio of 1.9:1, the antimicrobial effect of the co-cultured fermentation liquor of Bacillus amyloliquefaciens ACCC11060 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 45 publications
2
52
1
Order By: Relevance
“…In the present investigation, the L -Proline, N -pivaloyl- ethyl ester was found in only co-culture system and this might be responsible for the highest seed germination, biocontrol and plant growth (Table 5 and Figure 7). Similarly, Wu et al (2018) observed that the proline metabolism was induced in the co-culture of B. amyloliquefaciens ACCC11060 and T. asperellum using co-inoculation method.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In the present investigation, the L -Proline, N -pivaloyl- ethyl ester was found in only co-culture system and this might be responsible for the highest seed germination, biocontrol and plant growth (Table 5 and Figure 7). Similarly, Wu et al (2018) observed that the proline metabolism was induced in the co-culture of B. amyloliquefaciens ACCC11060 and T. asperellum using co-inoculation method.…”
Section: Discussionmentioning
confidence: 83%
“…The beneficial effect of T. asperellum and B. amyloliquefaciens includes protection against pathogens, growth promotion, induction of disease resistance, and production of bioactive compounds with antibiotic and antitumor properties (Brunner et al, 2005; Xie et al, 2018). The previous study on the co-cultivation of B. amyloliquefaciens and T. asperellum inhibited the growth of B. cinerea (Wu et al, 2018). Hence in the present study, stimulation of diverse cellular processes such as sporulation, secondary metabolism, enzyme productions in the co-culture of T. asperellum GDFS1009 and B. amyloliquefaciens 1841 were studied to evaluate its effect on biocontrol, and plant growth.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…have been conducted mainly in vitro. For instance, Wu et al 16 evaluated the antimicrobial effect of co-culturing Trichoderma asperellum GDFS1009 and Bacillus amyloliquefaciens ACCC11060 in BP broth (beef extract 0.3% and peptone 0.5%) finding the greatest effects against Botrytis cinerea by the supernatant from the co-culture than individual treatments. Other study demonstrated that in vitro co-culture of T. asperellum GDFS1009 and B. amyloliquefaciens 1841 induced the production of compounds not detected under pure cultures, attributed to the competition between them 17 .…”
mentioning
confidence: 99%
“…In simple cases, MSBCAs consist of only two strains, e.g., a fungus and a bacterium where one or both have biocontrol activities. A consortium consisting of Trichoderma asperellum GDFS1009 and Bacillus amyloliquefaciens ACCC1111060 was found to be more efficient against infection by Botrytis cinerea (the agent of gray mold disease) than the individual strains ( Wu et al, 2018 ). Similarly, when Trichoderma virens GI006 was combined with Bacillus velezensis Bs006, efficiency against Fusarium wilt of cape gooseberry was enhanced ( Izquierdo-García et al, 2020 ).…”
Section: Utilization Of Msbcas In Management Of Soil-borne Diseasesmentioning
confidence: 99%